2022
DOI: 10.1186/s11689-022-09458-6
|View full text |Cite
|
Sign up to set email alerts
|

Auditory processing in rodent models of autism: a systematic review

Abstract: Autism is a complex condition with many traits, including differences in auditory sensitivity. Studies in human autism are plagued by the difficulty of controlling for aetiology, whereas studies in individual rodent models cannot represent the full spectrum of human autism. This systematic review compares results in auditory studies across a wide range of established rodent models of autism to mimic the wide range of aetiologies in the human population. A search was conducted in the PubMed and Web of Science d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 155 publications
(554 reference statements)
0
5
0
Order By: Relevance
“…The onset response was also of similar amplitude between groups, for both the IC and AC (Figure 2E(i)). The resting EEG did not show the increase in gamma power reported in some other ASD mouse studies [95], including studies on Shank3b models [96]. The coherence between the IC and AC, which measures a linear subcortical contribution to AC field potential, was also similar between groups.…”
Section: Spontaneous and Evoked Eeg Signals In The Auditory Pathways ...mentioning
confidence: 51%
“…The onset response was also of similar amplitude between groups, for both the IC and AC (Figure 2E(i)). The resting EEG did not show the increase in gamma power reported in some other ASD mouse studies [95], including studies on Shank3b models [96]. The coherence between the IC and AC, which measures a linear subcortical contribution to AC field potential, was also similar between groups.…”
Section: Spontaneous and Evoked Eeg Signals In The Auditory Pathways ...mentioning
confidence: 51%
“…Several studies using electrophysiology and brain imaging data from ASD patients have revealed significant changes in sensory stimuli processing (Mamashli et al, 2017;Stickel et al, 2019;Pierce et al, 2021), specifically involving altered auditory perceptual capacity and deficits in auditory discrimination tasks, especially in the presence of noise (Gonçalves and Monteiro, 2023). In accordance with these findings, auditory alterations have been reported across several animal models of ASD, such as hyperacusis in Fmr1-KO rodents (Auerbach et al, 2021;Wilde et al, 2022), increased pitch discrimination abilities in Shank3B-KO mice (Rendall et al, 2019), increased thresholds for tone-evoked cortical responses in Mecp2 transgenic mice (Zhou C. et al, 2019), and auditory processing impairments in Cntnap2-KO rodents (Scott et al, 2018) as well as several Shank3 transgenic models (Castro and Monteiro, 2022). Our results expand these observations by revealing an auditory behavioral avoidance phenotype in Shank3 KO mice carrying a human ASD mutation in the Shank3 gene.…”
Section: Discussionmentioning
confidence: 66%
“…One such example of functional testing is the auditory brainstem response (ABR) test, typically used to assess hearing thresholds and the integrity of the auditory neural pathway. However, no consistent differences in ABR thresholds have been found between rodent models of ASD and WT animals ( Wilde et al, 2022 ). Regarding auditory behavioral tests, these typically tend to be related to conditioned/unconditioned or reflexive responses to sound.…”
Section: Discussionmentioning
confidence: 99%
“…Scale bars are approximate. Images were generated with brainrender [ 10 ] and taken from Wilde et al [ 8 ] under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution, and reproduction in any medium or format, as long as appropriate credit to the original author(s) and source are given. Furthermore, individuals diagnosed with ASD have a high prevalence of recurrent otitis media [ 11 , 12 ].…”
Section: Figurementioning
confidence: 99%